Corporate risk-taking and national governance quality: Empirical evidence from MENA emerging markets - Hamza Almustafa; Ploypailin Kijkasiwat; Ammar Jreisat; Somar Al-Mohamad; Audil Rashid Khaki (Cogent Business & Management, 2023)
Motivated by agency theory, this study seeks to understand the effect of the country-level national governance system on the extent of corporate risk-taking in the MENA region. The study employs a two-step generalized method of moments (GMM) approach to evaluate the influence of governance indicators on the firms' risk-taking behavior in 459 non-financial firms listed in eight emerging capital markets in the MENA markets (Iraq, Algeria, Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates) region from 2010 to 2019. The results suggest that countries with better national governance systems tend to incentivize businesses to undertake risky activities and projects, particularly due to low levels of government predation and efficient resource allocation. The results also imply that the economies with stronger governance policies and systems tend to have relatively stable macroeconomic environments and less uncertainty in the government policies, and therefore, the managers are motivated to undertake projects with higher risk-return metrics with a considerable potential to contribute to the country's economic growth.
Keywords: 650; corporate risk-taking; emerging markets; MENA region; National governance